Nadh Electrochemical Sensor Coupled by Dehydrogenase Enzymes - Yamanaka, Hideko; Mascini, Marco (Taylor & Francis, 1992)
A graphite electrode assembled in a flow cell has shown to be a good detector for NADH. Current is linearly dependent on -7-3 concentration in the range 10 -710-3 M without any mediator at the potential applied of 300 mV vs Ag/AgCl. Lactate and alcohol dehydrogenases were immobilized near to the electrode surface or in a reactor to obtain an NADH-based biosensor for lactate or alcohol. With lactate we succeeded to obtain a response only if the reactor was used and for alcohol a current proportional to the concentration was obtained either if the enzyme was immobilized in a membrane and placed near the electrode surface or when the enzyme was immobilized in a reactor form. By FIA procedures we could obtain fast responses and recoveries, but with a short linear range. © 1992, Taylor & Francis Group, LLC. All rights reserved.
Keywords: Alcohol; Bioreactors; Dehydrogenase; Enzymes; Graphite Electrodes; Lactate; NADH